Life-threatening experiences, posttraumatic stress disorder, and adaptation in Lithuanian men 17 years after military service in Afghanistan and the USSR - Domanskaitė-Gota, Vėjūnė; Gailienė, Danutė; Kazlauskas, Evaldas (Psichologija, 2006)
A sample of 268 Lithuanian men who served in the Soviet Army in 1979–1989 was investigated on theaverage 17 years after the service; the questionnaire was completed focusing on life-threatening expe-rience, posttraumatic stress reactions, and adaptation variables. The prevalence of posttraumatic stressdisorder was 30% in the group of the men who served in Afghanistan and 2% in the group of the menwho served in various places of the USSR. Lithuanian Afghanistan war veterans experienced significantlymore service-related and non-service-related traumatic events and conditions, and their adaptation afterthe service and nowadays were poorer than in the men who served in the USSR. Life-threatening expe-rience, PTSD and adaptation were correlated in both groups.
Keywords: PTSD; traumatic events; adaptation; Lithuanian Afghanistan war veterans